A pedagogia da alternância na integração de saberes no PROEJA Quilombola no Instituto Federal de Educação, Ciência e Tecnologia do Pará (IFPA) - campus Castanhal - SANTOS, Manuela Tavares (2013)
The text examines if and how the Pedagogy of Alternation contributes to the integration of knowledge in PROEJA Quilombola at the Federal Institute of Education, Science and Technology of Pará (IFPA) - Campus Castlebay. This is a qualitative research study, based on historical and dialectical materialism. Discusses how the Pedagogy of Alternation is materializing as methodological guidance for the integration of scientific knowledge with traditional knowledge in the training experience, the Proeja maroon? From the benchmarks of historical materialism, initially uses the literature review and then makes use of observations and interviews for the research field. Highlights positively as the most significant results of the research considerations that actually researched verified the enhancement of knowledge of the students, their participation in the processes of teaching and learning, the attempt of articulating knowledge with the reality of the students and the assumed reference form for family farms. Negatively highlights the separation between theory and practice in teaching, poor training of teachers in relation to the Pedagogy of Alternation, devaluation of reading as formative activity and difficulties in understanding and working with time-community. Concluded by stating there is an attempt of integration between the knowledge involved in the training of students Maroons, even with the existence of several problems in its implementation.